Economic and statistical study of the impact of digitalization on innovation activity of industrial organizations of the Union State - Galina A. Yasheva; Yulia G. Vailunova; Elena Yu. Vardomatskaya; Olga M. Sherstneva (Vestnik of Vitebsk State Technological University)
The article presents the results of a study on the impact of digitalization on the innovation activity of industrial organizations in the Republic of Belarus and the Russian Federation. The relevance of the research is due to the need to identify digitalization technologies that affect the innovation activity of organizations and establish digitalization strategies for industrial organizations within the Union State.